The Effect of Debt to Equity Ratio (DER) and Sales Growth on ROA of Manufacturing Companies listed on the IDX for the 2021-2024 Period - Fajar Japar Sodik; Gusganda Suria Manda (Pusat Riset dan Inovasi Nasional, 2025)
Financial performance is a crucial indicator in evaluating business stability and success, with Return on Assets (ROA) as one of the main profitability measures. This study aims to examine the effect of Debt to Equity Ratio (DER) and Sales Growth on ROA in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2024. Using a quantitative approach with a comparative causal design, this study applied purposive sampling to 12 manufacturing companies from the paper and cement subsectors, resulting in 48 observations. Data analysis was conducted using multiple linear regression with SPSS 26. The research findings show that Sales Growth has a positive and significant effect on ROA with a coefficient of 0.082 (sig. 0.004), while DER has a negative and significant effect on ROA with a coefficient of -2.277 (sig. 0.000). Simultaneously, both variables have a significant effect on ROA with an R Square of 0.422, indicating that 42.2% of ROA variation can be explained by the model. These results imply that manufacturing companies need to optimize capital structure by managing debt levels wisely while implementing sustainable sales growth strategies to im- prove profitability performance.